The Role of Prognosis Research in Projecting Healthcare Expenses. - Mendoza Saltiel Busch Busch, Rebecca; Busch, Andrew; Garzillo, Thomas; Ramsey, Dena (Journal of Nurse Life Care Planning)
Life Care Planners may find themselves working with a niche industry of healthcare professionals that are involved in projecting healthcare services in the context of personal injury cases. Healthcare services received and those likely needed in the future in the context of a personal injury case are often reviewed and allocated by medical audit/ billing specialists as well as life care planners. Prospective healthcare service determinations are typically determined by a life care planner and supported by collaboration with treating providers to help them understand the specific future care needs required to address the injury over the life expectancy of the injured party. Life care planners may incorporate the spirit of a case management function; however, this type of projected services and cost research often involves obtaining specific details as to what procedure codes would represent the projected services. In addition, life care planners may rely on prognosis research in their discussions with the treating providers to support and strengthen the future care allocations.